(untitled) (diségno, 2024)
The search for the spatial and formal quality of architecture still finds its best referent in the physical model. Reproducing the material texture of built architecture communicates the idea of form and volume that is presented in real space. Models, in the construction of image sequences, reproducing existing or designed buildings, fulfill the task of tools for knowledge. The underlying rules of architecture materialize, deconstruct and reassemble in a dialectical process in which thought takes form and becomes space. Representing an architecture by separate parts, selectively describing its characteristics, reducing them to fragments of compositional units, and then reassembling them in their configuration, becomes a useful cognitive exercise in the investigation of architecture. A tool of study, investigation and interpretation, the model represents an intermediate figure between the imaginary and reality. In the form of ideation it is anticipation of spatial organizations; in the form of representation of the existing it becomes a process of control and analysis.